L’apport des analyses 14C à l’étude de la nécropole de l’âge du Bronze de“ La Croix de la Mission ” à Marolles-sur-Seine - Rebecca Peake; Valérie Delattre (Revue Archéologique du Centre de la France)
Fourteen of the 41 burials of the “ la Croix de la Mission ” Bronze Age cemetery at Marolles-sur-Seine have recently been carbon dated by the Lyon (France) and Groningen (Netherlands) laboratories. These new dates confirm the site’s occupation for more than 1000 years from 2000 BC to 800 BC and determine more precisely the different cultural and chronological phases of the cemetery illustrated by the great range of its burials.